If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5s + 1) + -1(2s + 3) = n Reorder the terms: (1 + 5s) + -1(2s + 3) = n Remove parenthesis around (1 + 5s) 1 + 5s + -1(2s + 3) = n Reorder the terms: 1 + 5s + -1(3 + 2s) = n 1 + 5s + (3 * -1 + 2s * -1) = n 1 + 5s + (-3 + -2s) = n Reorder the terms: 1 + -3 + 5s + -2s = n Combine like terms: 1 + -3 = -2 -2 + 5s + -2s = n Combine like terms: 5s + -2s = 3s -2 + 3s = n Solving -2 + 3s = n Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 3s = 2 + n Combine like terms: -2 + 2 = 0 0 + 3s = 2 + n 3s = 2 + n Divide each side by '3'. s = 0.6666666667 + 0.3333333333n Simplifying s = 0.6666666667 + 0.3333333333n
| 4x-9=7+13 | | 2a-9=4(3a+1)-7 | | 5.82+y=-10.5 | | .33x=470000-x | | 11(j-2)-6(2-j)+2(j-2)=0 | | -4y-2x+6=0 | | 0.04(3t-8)=0.12(t-1)-0.20 | | .8n+.2=1.2n+.4 | | 0.6x+0.2=0.8x-0.2 | | x+(x+4)=328 | | 5(x-2)-18=42 | | 10x-11=29 | | 4.13x+3.18=3.6x | | 2a^2-26a+84=00 | | 830=119x-237634 | | 9(y-1)+8=32 | | z^2-3z+2iz+1-3i=0 | | 3(2+w)-4w=w+16 | | 5x-2(x-1)=-4+5x+8 | | (4-z)(3z+2)=0 | | 0.05-0.02(x+2)=-0.03(3-x) | | 9/b-3/b | | ln(x^2-6)=ln(x) | | (7x-5)+(x+3)=90 | | 3x^2+bx+6=0 | | 2.8x-4.5+5x=2.8+6.2x-10.7 | | 6t-10=20+t | | 0.14(y-7)+0.06y=0.04y-2.1 | | y=4x(-2x^2-9x+3) | | -34+2x=68+8x | | 6(h-4)=h | | 7r-9=16+2r |